Health commodities logistics management information system performance at public health facilities of Amhara region, Ethiopia - Mekonen, Zelalem Tilahun; Cho, Denny J.; Fenta, Teferi Gedif (Frontiers in Public Health, 2025)
IntroductionEnsuring equitable access to essential medicines is a major global health challenge, particularly in low- and middle-income countries. Effective supply chain management and Logistics Management Information Systems (LMIS) are crucial for addressing these challenges. Despite substantial efforts, significant LMIS implementation issues continue, especially in Ethiopia.ObjectivesThe study aimed to evaluate the performance of health commodities logistics management information systems at public health facilities in the Amhara Region, Ethiopia.MethodsThe study conducted in public health facilities of the Amhara region in Ethiopia used a quantitative methods approach. The region is supplied by four Ethiopian Pharmaceutical Supply Service hubs. A total of 102 facilities, selected through stratified random sampling, were included in the study. Data were collected through record review and and observation using data abstraction checklists to evaluate the LMIS forms availability, utilization, supply, and report timeliness.ResultsInfrastructure challenges were noted, including inconsistent power supply and limited internet access, with only 42.2% having internet connectivity. LMIS performance varied, with high availability and utilization of forms like the IFRR and RRF but lower rates for some forms and digital systems. Reporting and feedback mechanisms were generally adequate, though only 37.3% of facilities received periodic written feedback from higher levels of the healthcare system.Conclusion and recommendationThe evaluation of the LMIS in Amhara Region’s public health facilities shows notable achievements in the widespread use of LMIS forms and reporting systems. However, ongoing challenges such as unreliable infrastructure, poor internet connectivity, and insufficient human resources impede effective LMIS performance. Addressing these issues, digitalization of the LMIS, strengthening feedback mechanisms, and supervisory support will enhance LMIS performance and improve health outcomes.